Child temperament, child-parent relationship and anxiety among children in childcare centers in urban Selangor, Malaysia - Low, Biam Hong (2017)
Child anxiety is defined as the feeling of being afraid and out of control. Even though almost every child experiences anxiety, yet when it is persistent it may develop into an anxiety disorder and will eventually affect one’s developmental outcome. In Malaysia, the worsening trend of child anxiety has raised the attention and concern of the government and the public in recent years. According to the National Health and Morbidity Survey (NHMS) in 2011, there are one million Malaysian children aged between 5 to 15 years old who are suffering from anxiety, stress, depression and mental health issues. However, only a handful of studies in Malaysia have been conducted on child anxiety and the factors that contribute to it. To address this paucity, the present study was primarily conducted to determine the relationships between child temperament, child-parent relationship and anxiety among children in childcare centers in urban Selangor, Malaysia. Furthermore, this study also determines the mediating role of child-parent relationship on child temperament and anxiety. A total of 319 mothers with children aged between three to six years old from childcare centres in urban Selangor were identified using Multi-Stage Cluster sampling. Data was collected using a self-administered questionnaire. EAS Temperament Survey for Children (Buss & Plomin, 1984), Child Parent Relationship Scale (Pianta, 1998) and Spence Preschool Anxiety Scale (Spence & Rapee, 1999) were utilised to assess child temperament, child-parent relationship and child anxiety symptom respectively. The findings revealed that 14.1% of mothers reported that their child exhibited a high level of child anxiety symptoms. Findings from Pearson Product-Moment Correlation analyses showed that child’s emotionality is significant negatively associated with closeness child-parent relationship (r = -.33, p < .01). Emotional children also had significant higher levels of child’s anxiety symptom (r = .25, p < .01). The study revealed that child’s sociability was shown to have positive association with closeness (r = .18, p < .01) child-parent relationship. A significant negatively association was found between child’s sociability and child’s anxiety symptom (r = -.15, p < .01). Child shyness was found to be significant negatively correlated with closeness of the child-parent relationship (r = -.21, p < .01). Close child-parent relationship had significant negative relationship with child’s anxiety symptom (r = -.52, p < .01). Multiple regression analysis showed that closeness of the child-parent relationship was the highest unique contribution to the prediction of child’s anxiety (β = -.49, p < .01). Child emotionality and anxiety were fully mediated by the closeness of the child-parent relationship. The relationship between child sociability and anxiety were fully mediated by closeness child-parent relationship. The study provides valuable information on how child temperament influences child anxiety through child-parent relationships. These findings may contribute to the implication of theory by shedding light on the role of child temperament and child-parent relationship and how it affects child anxiety, particularly for children in childcare centres. In terms of practical implication, the findings may help relevant parties to have a better understanding on child anxiety.